2006
DOI: 10.1002/ijc.21914
|View full text |Cite
|
Sign up to set email alerts
|

Noninvasive diagnosis of nasopharyngeal carcinoma: Nasopharyngeal brushings reveal high Epstein‐Barr virus DNA load and carcinoma‐specific viral BARF1 mRNA

Abstract: Nasopharyngeal carcinoma (NPC) is the most prevalent ENTtumour in Indonesia. We investigated the primary diagnostic value of Epstein-Barr virus (EBV) DNA load and mRNA detection in noninvasive nasopharyngeal (NP) brushings, obtained prospectively from consecutive Indonesian ENT-patients with suspected NPC (N 5 106) and controls. A subsequent routine NP biopsy was taken for pathological examination and EBER-RISH, yielding 85 confirmed NPC and 21 non-NPC tumour patients. EBV DNA and human DNA load were quantifie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
130
0
5

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 106 publications
(151 citation statements)
references
References 45 publications
13
130
0
5
Order By: Relevance
“…A mutation in the BARF1 gene, which will allow the direct testing of BARF1 function in infection, was described recently in the EBV-related rhesus lymphocryptovirus (8). Finally, the BARF1: M-CSF structure provides additional evidence that BARF1 modulates M-CSF-mediated immune responses and may provide a basis for beginning to understand any putative role of BARF1 in the alteration of cellular growth (17,(29)(30)(31)(32).…”
Section: Indirect Interference Of Barf1 With Mcsf:fms Binding and Sigmentioning
confidence: 94%
“…A mutation in the BARF1 gene, which will allow the direct testing of BARF1 function in infection, was described recently in the EBV-related rhesus lymphocryptovirus (8). Finally, the BARF1: M-CSF structure provides additional evidence that BARF1 modulates M-CSF-mediated immune responses and may provide a basis for beginning to understand any putative role of BARF1 in the alteration of cellular growth (17,(29)(30)(31)(32).…”
Section: Indirect Interference Of Barf1 With Mcsf:fms Binding and Sigmentioning
confidence: 94%
“…Indeed, T-cell cultures generated with conventional protocols are virtually devoid of BARF1-specific effectors. Considering that BARF1 is expressed by the majority of NPCs from both endemic and nonendemic areas (13)(14)(15)(16), the availability of a protocol able to generate EBV-specific CTLs efficiently targeting BARF1 may also enhance the still unsatisfactory rates of clinical responses obtainable by adoptive immunotherapy in this setting (9,10).…”
Section: Discussionmentioning
confidence: 99%
“…The oncogenic EBV protein BARF1 is expressed in the majority of NPC cases (13)(14)(15)(16) and may constitute an attractive therapeutic target. In particular, we have previously demonstrated that NPC patients show strong spontaneous CD4…”
Section: Introductionmentioning
confidence: 99%
“…In addition, other pathogenic factors that are enriched in EBV exosomes such as EBV DNAs, EBV mRNAs and EBV miRNAs have also been shown to be potential biomarkers for EBV cancer diagnosis [56][57][58][59] ( Table 2). Using quantitative PCR (qPCR), Yip and colleagues showed that high-EBV DNAs could be detected in plasma/serum of NPC patients at late stages of disease and the viral loads were associated with poor survival or frequent relapse in NPC patients [56,59].…”
Section: Exosomes As Biomarkersmentioning
confidence: 99%